2013
DOI: 10.1016/j.virol.2013.06.026
|View full text |Cite
|
Sign up to set email alerts
|

Glycolytic control of vacuolar-type ATPase activity: A mechanism to regulate influenza viral infection

Abstract: As new influenza virus strains emerge, finding new mechanisms to control infection is imperative. In this study, we found that we could control influenza infection of mammalian cells by altering the level of glucose given to cells. Higher glucose concentrations induced a dose-specific increase in influenza infection. Linking influenza virus infection with glycolysis, we found that viral replication was significantly reduced after cells were treated with glycolytic inhibitors. Addition of extracellular ATP afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
112
0
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(122 citation statements)
references
References 27 publications
2
112
0
8
Order By: Relevance
“…STF-31, used in this study, is one of the promising Glut-1 inhibitors which have been shown to selectively kill renal carcinoma cells (25,43). Interestingly, there are reports showing that high glucose levels also enhance virus infection of host cells, supporting viral replication and maintenance of latency infection (44)(45)(46). Activation of Glut-1 transcription is a novel property of LMP1 not previously reported.…”
Section: Discussionmentioning
confidence: 65%
“…STF-31, used in this study, is one of the promising Glut-1 inhibitors which have been shown to selectively kill renal carcinoma cells (25,43). Interestingly, there are reports showing that high glucose levels also enhance virus infection of host cells, supporting viral replication and maintenance of latency infection (44)(45)(46). Activation of Glut-1 transcription is a novel property of LMP1 not previously reported.…”
Section: Discussionmentioning
confidence: 65%
“…We previously reported greater uptake of FDG in the right caudal lung compared to that in other lobes, where we and others have found increased viral replication and neutrophil infiltration (29,30,33). Another hypothesis to explain increased FDG uptake is that IAV increases cellular glucose metabolism (99). We found that infection with IAV isolates caused an increase in FDG uptake by immortalized human epithelial cell lines (A549) in vitro but not by differentiated human bronchial epithelial cells (16HBEoϪ) (29,58; also data not shown).…”
Section: Discussionmentioning
confidence: 76%
“…We found that infection with IAV isolates caused an increase in FDG uptake by immortalized human epithelial cell lines (A549) in vitro but not by differentiated human bronchial epithelial cells (16HBEoϪ) (29,58; also data not shown). Increased glucose levels promote the acidification of cellular endosomal compartments, a step required for IAV infection of cells (99,100). In hospital clinics, FDG is used to detect metabolically active tumors throughout the body, including the lungs, as it is taken into cells through glucose transporters and accumulates (71,101,102).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, V-ATPase mutations that impair binding to phosphofructokinase-1 are associated with distal renal tubular acidosis (24), and V-ATPase regulation by glycolysis plays a role in viral infections (40) and the metabolic switch in cancers (41,42). It has been proposed that glycolytic enzymes form a supercomplex with V-ATPase that funnels ATP directly to VATPase and propels proton transport (21,24,32,34,37,43).…”
Section: Connecting Glucose Metabolism To V-atpase Assemblymentioning
confidence: 99%